Income redistributive effect of health care financing in Zambia - Mulenga, Arnold (Health Economics Unit, 2015)
Equity in health care financing and progress towards universal health coverage (UHC) have increasingly received recognition and growing attention for their potential to improve health outcomes globally. However, most low income countries and in particular those in sub-Saharan Africa which have borne the greater share of global disease burden have had relatively lesser success in their endeavours to improve their health care financing systems. It is only a few that have made considerable progress towards universal health coverage. Zambia, a developing country struggling with income inequalities and poor progress to achieving universal health coverage, is no exception. The current discussion on countries moving toward universal health coverage, however, requires an understanding of the impact of the prevailing health care financing mechanisms on income distribution. Investigation of an overall income redistributive effect of health care financing thus requires assessing health care financing in relation to the principles of contributing to financing health care according to ability to pay. Zambia is currently considering major health systems reforms toward a universal health system. Health care financing system in Zambia is however faced with numerous challenges that must be addressed prior to meeting this goal. To promote the goal of achieving universal health coverage, there is a need to measure the extent of the redistributive effect of the current health care financing mechanisms. This allows identifying which health care financing mechanisms provide financial protection and promote universal health coverage in the country. With this growing focus on the goal of universal health coverage (UHC), health care financing mechanisms should not only relate to who pays and who receives the benefit, but also to their effects on income distribution. This is because financing of health care may have redistributive effects and equity consequences. This income redistribution may be intended or unintended. Even in the latter case, policy makers may be interested in the degree to which it occurs. This is because it has consequences for the distribution of goods and services other than health care and, ultimately, for welfare. This study investigates the extent to which the current health care financing in Zambia redistributes income, particularly whether or not it reduces income inequality. The study seeks to evaluate an overall pattern of income redistributive effect of the current health care financing mechanisms. It specifically assesses the income redistributive effect of two broad health care financing mechanisms; general tax and out of pocket (OOP) payments. Using a standard procedure for analyzing income redistribution of health care financing in Zambia, the study decomposes the income redistributive effect of each of the two broad health care financing mechanisms into the vertical, horizontal and reranking components.